2011
DOI: 10.1099/vir.0.036590-0
|View full text |Cite
|
Sign up to set email alerts
|

Outbreak of swine influenza in Argentina reveals a non-contemporary human H3N2 virus highly transmissible among pigs

Abstract: Sporadic outbreaks of human H3N2 influenza A virus (IAV) infections in swine populations have been reported in Asia, Europe and North America since 1970. In South America, serological surveys in pigs indicate that IAVs of the H3 and H1 subtypes are currently in circulation; however, neither virus isolation nor characterization has been reported. In November 2008, an outbreak of respiratory disease in pigs consistent with swine influenza virus (SIV) infection was detected in Argentina. The current study describ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 17 publications
(25 reference statements)
2
36
0
Order By: Relevance
“…In 2008, the farm was positive for IAV where a wholly human-origin H3N2 virus was isolated from 40–50 days old pigs [8]. In October 2009, a novel IAV was identified, a reassortant with HA and NA gene segments from an H1N1 of the δ2 cluster and internal gene segments from an H1N1p virus [17].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2008, the farm was positive for IAV where a wholly human-origin H3N2 virus was isolated from 40–50 days old pigs [8]. In October 2009, a novel IAV was identified, a reassortant with HA and NA gene segments from an H1N1 of the δ2 cluster and internal gene segments from an H1N1p virus [17].…”
Section: Resultsmentioning
confidence: 99%
“…In these farms, IAV infections are considered a nursery problem mostly affecting successive batches [3]. Previous serological and virological characterization studies showed that influenza virus strains that circulate in pigs in Argentina are not related to those reported in pigs elsewhere in the world with the exception of the H1N1p virus [3,8,17]. Upon independent multiple introductions of the H1N1p virus in pig populations around the world, multiple reassortment events have been and continue to take place with previously circulating swine IAV strains [1720].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, our study did not consider pH1N1 viruses because prior studies provide global estimates of the frequency of human-to-swine transmission of these viruses since 2009 (16). Taken together, these data make it clear that our estimate of human-to-swine transmission represents a conservative, lowerbound estimate, and increased swIAV sequencing on a global scale is required to capture the full scale of human-to-swine transmission (43)(44)(45)(46).…”
Section: Discussionmentioning
confidence: 99%
“…Central to the global evolution of genetic diversity of swIAVs is the repeated introduction of IAVs of human seasonal virus origin in swine [21,3641]. In contrast to major pandemic influenza events that last 1–3 years and occur sporadically, seasonal influenza viruses are associated with annual epidemics in humans that occur in winter in temperate regions.…”
Section: Humans As Major Sources Of Influenza Virus Diversity In Swinementioning
confidence: 99%